Faktor Dana Pihak Ketiga, Tingkat Suku Bunga Kredit, dan Kredit Bermasalah dalam Menentukan Profitabilitas Bank di Bursa Efek Indonesia - Vianisa Cornelia Sukoco; Nursiam (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze and test the effect of third-party funds, credit interest rates, and non-performing loans on the profitability of banks listed on the Indonesia Stock Exchange for the period 2021–2023. The approach used is quantitative with hypothesis testing through multiple linear regression analysis. The population in this study were all banking sector companies on the Indonesia Stock Exchange for the period 2021–2023. The independent variables of this study are Third Party Funds, Credit Interest Rates, Non-Performing Loans, while the dependent variable is Profitability. This study uses a purposive sampling method in sampling. A total of 96 companies have met the criteria as observation units. The data used are secondary data obtained through annual financial report documentation. The results of the study indicate that third-party funds, credit interest rates, and non-performing loans have a significant effect on bank profitability, with all hypotheses accepted based on a significance value <0.05. These findings indicate that these three variables have an important role in determining the level of bank profitability.